Denosumab in Giant Cell Tumor of Bone: Current Status and Pitfalls - Li, Hengyuan; Gao, Junjie; Gao, Youshui; Lin, Nong; Zheng, Minghao; Ye, Zhaoming (Frontiers in Oncology, 2020)
Denosumab is a monoclonal antibody against RANK ligand for treatment of giant cell tumor of bone (GCTB). Clinical trials and case series have demonstrated that denosumab is relevant to beneficial tumor response and surgical down-staging in patients of GCTB. However, these trials or case series have limitations with a short follow-up. Recent increasing studies revealed that denosumab probably increased the local recurrence risk in patients treated with curettage. This may be caused by the thicken bone margin of tumor that trapped tumor cells from curettage. The direct bone formation by tumor cells in the margin after denosumab treatment also contributed to the local recurrence. In vitro studies showed denosumab resulted in a cytostatic instead of a true cytotoxic response on neoplastic stromal cells. More importantly, denosumab-treated GCTB exhibited morphologic overlap with malignancy, and a growing number of patients of malignant transformation of GCTB during denosumab treatment have been reported. The optimal duration, long term safety, maintenance dose and optimum indications remain to be elucidated. With these concerns in mind, this review warns that the denosumab therapy of GCTB should be applied with caution.